Changes in renal venous flow and liberation from renal replacement therapy in patients with acute heart failure - Husain-Syed, Faeq; Vaughan, Lisa; Bauer, Pascal; Tello, Khodr; Richter, Manuel J.; Gall, Henning; De la Espriella, Rafael; Cobo Marcos, Marta; Núñez, Julio; Rangaswami, Janani; Romero-González, Gregorio; Yücel, Gökhan; et al. (Cardiorenal Medicine, 2025)
Introduction: In acute heart failure (AHF), the factors associated with successful renal replacement therapy (RRT) discontinuation are largely undefined. We hypothesized that improvements in Doppler-derived renal venous flow (RVF) waveforms may serve as indicators of recovering cardiorenal function associated with successful liberation from RRT. Methods: We performed a post hoc analysis of a prospective cohort study involving inpatients with AHF undergoing serial renal Doppler evaluations. Patients who received acute RRT were retained for analysis, with Doppler assessments conducted both before RRT initiation and after discontinuation. Successful RRT discontinuation was defined as RRT cessation without relapse for at least 14 days. Logistic regression was used to evaluate the association between changes in RVF markers - including intra-renal venous flow (IRVF) and the renal venous stasis index (RVSI) - and RRT discontinuation, along with echocardiographic and clinical data from pre- to post-RRT Doppler measurements. Results: Overall, 10/53 (19%) patients successfully discontinued RRT. Increases in the severity of IRVF patterns and RVSI were negatively associated with RRT discontinuation (IRVF per 1-pattern increase in severity: OR 0.01, 95% CI, <0.001-0.11; p < 0.001; RVSI per 0.1-unit increase: OR 0.11, 95% CI, 0.03-0.48; p < 0.001). Additionally, improvements in right ventricular function markers, such as the TAPSE/sPAP ratio (per 0.1 mm/mm Hg increase: OR 1.83, 95% CI, 1.03-3.32; p = 0.049), were associated with higher odds of RRT discontinuation. Conclusions: In AHF patients requiring acute RRT, improvements in RVF were associated with successful RRT discontinuation. Serial RVF assessment may offer a noninvasive means of capturing dynamic changes in cardiorenal syndrome physiology and renal recovery. Larger studies with more frequent and appropriately timed Doppler assessments are needed to determine whether RVF monitoring may guide RRT management in AHF.
Online veröffentlicht: 10. Juni 2025
Gesehen am 26.08.2025